Identification of CYP2C9, VKORC1 genotypes and recommendation of warfarin dose for Vietnamese cardiovascular patients - Dang Ton, Nguyen; Thanh Hoa, Nguyen Thi; Phan Anh, Nguyen; Phuong Nhung, Vu; Bich Thao, Le Thi; Hai Ha, Nguyen (Vietnam Journal of Biotechnology, 2020)
Warfarin is a well-known anticoagulant that capable of reducing the activity of vitamin K-dependent clotting factors. It has been widely used for cardiovascular patients. However, patient’s genotype of CYP2C9 and VKORC1 remarkably affects the metabolism of warfarin. This study aims to identify the CYP2C9 and VKORC1 genotypes of 96 Vietnamese patients suffering cardiodynia or myocardial infarction and establish their daily warfarin dose. The PCR-RFLP method was used to identified the CYP2C9*2, CYP2C9*3 and VKORC1 alleles. The result indicated that allelic frequencies for CYP2C9*3 were observed at 3% of investigated patients while CYP2C9*2 alleles and genotypes were not detected in this study population. Allele frequency of VKORC1 (c. -1639G>A) was observed at 84%. Base on the CYP2C9 and VKORC1 genotypes, we recommended the daily warfarin dose for of these patients.